A grounded theory study of the clinical use of the nursing process within selected hospital settings. - O'Connell, Beverly O. (Curtin University, 1997)
The nursing process is the espoused problem solving framework that forms the basis of the way in which patient care is determined, delivered, and communicated in a multiplicity of health care settings. Although its use is widespread in educational and clinical settings, some nurse clinicians display negative attitudes towards the use of the nursing process. They claim that both the structure and language that underpins this process is cumbersome and unreflective of the way in which nursing care is planned and delivered. To date, there has been no study cited that has examined its use within a clinical setting and determined if and how the nursing process is being used and whether there is substance in the clinicians' claims. Additionally, some of the research on problem solving has used laboratory based designs that are limited as they are not sensitive to contextual factors that affect the use of a problem solving process, nor are they sensitive to the efficacy of the communication process. As patient care involves many nurses working under diverse contextual conditions, these factors need to be taken into consideration when studying this phenomenon.Using grounded theory methodology, this study examined the clinical application of the nursing process in acute care hospital settings. Specifically, it sought to answer the following two questions: (1) How is the nursing process used by nurse clinicians in acute care hospital settings? and in the absence of its use, (2) How is nursing care determined, delivered, and communicated in acute care hospital settings in Western Australia?Data were obtained from semi-structured interviews with predominantly nurse clinicians, patients, and patients' relatives, as well as participant field observations of nurse clinicians, and in-depth audits of patient records. Textual data were managed using NUD-IST and analysed using constant comparative method. Data generation and analysis proceeded simultaneously using open coding, theoretical coding, and selective coding techniques until saturation was achieved. This resulted in the generation of a substantive theory explaining clinical nursing in acute care hospital settings.The findings of this study revealed several problems with the clinical application of the nursing process. It also revealed a process used by nurses to overcome many difficulties they experienced as they tried to determine, deliver, and communicate patient care. Specifically, nurses in this study experienced the basic social problem of being in a state of "Unknowing". Properties and dimensions of unknowing were found consistently in the data and this problem was labelled as the core category. This state of "unknowing" was linked to a number of factors, such as, the existence of a fragmented and inconsistent method of determining and communicating patient care and work conditions of immense change and uncertainty. In order to deal with this problem, the nurses in this study used a basic social process termed: "Enabling Care: Working through obscurity and uncertainty". The first phase of the core process, termed: Putting the pieces together: making sense, involved four subprocesses. These subprocesses were labelled: drawing on the known, collecting and combining information, checking and integrating information, and sustaining communication. The second phase of the core process was termed Minimising uncertainty. It involved three subprocesses which were named: adapting work practices, taking control, and backing-up.The findings of this study have implications for nursing practice, research, theory, and education, as it exposes problems with the clinical application of the nursing process in acute care settings. In addition, it further explicates a substantive theory that describes a process of nursing used by nurses in these settings. As the articulated process was supported by a number of studies and opinions of nurse scholars it is worthy of being considered as being foundational to an understanding of a process of nursing used in acute care hospital settings in Western Australia.